Understanding the concept of Islamic hospitality: a move towards Malaysia hotel's sustainability/ Nor Amira Mohd Razali ... [et al.] - Mohd Razali, Nor Amira; Awang, Khairil Wahidin; Mohd Yusof, Mohd Fadil; Hasan, Hazriah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The increasing number of the world's Muslim population is likely to increase Muslim visitors' numbers and intensify the demand for Muslim-friendly products and services within the hospitality industry. The Malaysian government introduced the Muslim-friendly Accommodation Recognition (MFA) as one of the initiatives to tap the Muslim market. However, the small number of hotels participating in the recognition campaign indicates the idea is not well received by practitioners. Furthermore, the current COVID-19 pandemic aftermath has caused some hotels to either permanently shut down or consider temporary closure of their operations. This study aims to examine the contribution of Islamic hospitality practices towards sustaining Malaysia's hotel sector. A qualitative approach will be applied where the focus will be on the Islamic hotel sector. The indepth interview technique will be used for data collection and the data gathered will be analysed using thematic analysis with the help of Atlas.ti 8 software. The outcome of this study is expected to add to the existing literature on religion-based hospitality, specifically from the Islamic perspective. In addition, it will increase the understanding of the Islamic hospitality concept and practices implemented by the hotel sector in Malaysia.